E-module based on ethnomathematics comics with the ICARE model to improve students' mathematical representation skills - Ayunda Argadinata; Hevy Risqi Maharani (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop an ethnomathematics comic-based e-module by applying the ICARE model to improve students' mathematical representation skills. The ICARE model consists of the Introduction, Connection, Application, Reflection, and Extension stages. The research approach used is Research and Development (R&D) with the ADDIE development model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of the study were grade VIII students at a junior high school that had adopted the Merdeka Curriculum. Before being tested on a small scale, the e-module was first validated by experts in the field of materials and media to ensure its feasibility. The research instruments included a validation questionnaire, a test to measure mathematical representation skills, and a questionnaire used to collect student and teacher responses. The results of the study showed that the e-module developed met the criteria of being valid, practical, and effective in improving students' mathematical representation skills. Students responded positively to the e-module because the material presented was more interesting, based on local culture, and helped them understand the concept more deeply. Thus, the e-module based on ethnomathematics comics with the ICARE model can be an alternative innovative teaching material in mathematics learning.